Factors Influencing Help-Seeking Behavior in Women with Postpartum Depression - Wright, Amelia; Mata, Giselle (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the psychological, interpersonal, structural, and systemic factors influencing help-seeking behavior among women experiencing postpartum depression in Greece.Methods and Materials: A qualitative research design was employed using semi-structured, in-depth interviews with 21 women diagnosed with postpartum depression within the first year after childbirth. Participants were recruited using purposive sampling, and data collection continued until theoretical saturation was reached. Interviews were transcribed verbatim and analyzed thematically using NVivo 14 software. Thematic analysis followed Braun and Clarke’s six-step framework. Rigor was ensured through independent coding, member checking, and maintenance of reflexivity throughout the research process.Findings: Thematic analysis revealed four main categories: (1) Psychological and Emotional Barriers, including fear of stigma, internalized guilt, and denial of illness; (2) Interpersonal and Social Influences, such as spousal support, family dynamics, and cultural expectations; (3) Structural and Systemic Barriers, including limited accessibility, financial constraints, and mistrust in healthcare services; and (4) Facilitators of Help-Seeking, such as empathetic healthcare professionals, psychoeducation, community networks, and positive prior experiences with mental health care. Participants’ narratives highlighted a complex interplay between internal struggles and external conditions that either hindered or encouraged their willingness to seek professional help.Conclusion: Help-seeking behavior in women with postpartum depression is shaped by a constellation of interrelated psychological, social, and systemic factors. Addressing these barriers requires a multidimensional approach that includes stigma reduction, mental health literacy, empathetic provider training, and culturally sensitive, accessible services. Interventions should empower women to recognize and validate their emotional experiences while facilitating supportive environments that normalize seeking care during the postpartum period.